Appraisal of China's Response to the Outbreak of COVID-19 in Comparison With SARS - Jiajia Li; Jiajia Li; Shixue Li; Shixue Li; Wuchun Cao; Wuchun Cao; Zhongli Wang; Zhongli Wang; Zhuohui Liang; Wenhao Fu; Wenhao Fu; Jinfeng Zhao; et al. (Frontiers Media S.A., 2021)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2, was first reported in Wuhan, China, in December 2019 and has since become a pandemic. The COVID-19 containment measures were comparable to those used with severe acute respiratory syndrome (SARS), although these were stricter and more organized, and were initiated earlier and on a larger scale. Based on the lessons learned from SARS, the Chinese government acted aggressively in response to COVID-19, through a unified and effective commanding system, using law-based and science-driven strategies, and coordinated deployment of medical resources. Additionally, the application of high-tech measures, traditional Chinese medicine, and hierarchical medical systems also played an important role in control measures. Despite the remarkable performance, the initial delay in response suggests that the coordination between public health and medical services, reserve and coordination of emergency materials, and capacity for disease control and prevention need to be strengthened.